Developing Higher Order Thinking Skills Assesment Instruments on Invironmental Pollution Material for Class VII - Asra Indah; Azrita Azrita; Rona Taula Sari (Journal of Biological Science and Education, 2021)
This study aim to produce a valid and practical assessment instrument for higher order thinking skills on environmental pollution material at the C4-C6 cognitive level. The background of this research is that the questions made by the teacher are still at the C1-C3 level and there are still obstacles for teachers in developing higher order thinking skills assessment instruments, while in the 2013 curriculum teachers are required to be able to provide questions in the C4-C6 domain. This type of research is research development (Research and Development) which is a research method used to produce certain products. This type of research uses 3 stages of the 4-D model, namely the define, design and develop stages.Based on the research conducted, a very valid assessment instrument of 3,32 was produced by the validator, the empirical validity there were 30 valid questions and 10 invalid questions, the reliability in this study was 0,77 with the category of reliability, 94,79% teacher practicality and practicality. students amounted to 80,80%, the difficulty level of the questions was between 0,31 to 0,70 with moderate criteria and the question difference had sufficient criteria. This research can be used as a reference for other researchers related to the development of higher order thinking skills assessment instruments.